PENGARUH CURRENT RATIO DAN DEBT TO EQUITY RATIO TERHADAP PERTUMBUHAN LABA DENGAN UKURAN PERUSAHAAN SEBAGAI VARIABEL MODERASI: STUDI KASUS PADA PERUSAHAAN MAKANAN DAN MINUMAN YANG TERDAFTAR DI BURSA EFEK INDONESIA - Avianty, Hani Dyah; Kristianto, Djoko (Gapenas Publisher, 2025)
The purpose of this research is to analyze the significance of the effect of current ratio and debt to equity ratio on earnings growth and analyze the significance of company size in moderating the effect of current ratio and debt to equity ratio on earnings growth. The scope of the research uses a quantitative approach to food and beverage companies listed on the Indonesia Stock Exchange in 2019 - 2023 with a sample of 15 companies used purposive sampling technique. Data collection techniques used documentation. Data analysis used multiple linear regression and Moderated Regression Analysis (MRA). The results showed that the current ratio has a positive and significant effect on profit growth. Debt to equity ratio has a negative and significant effect on profit growth. Current ratio has no significant effect on profit growth with company size as a moderating variable. Debt to equity ratio has a significant effect on earnings growth with company size as a moderating variable